The Prognostic and Clinicopathological Roles of PD-L1 Expression in Colorectal Cancer: A Systematic Review and Meta-Analysis - Li, Yan; He, Meizhi; Zhou, Yaoyao; Yang, Chen; Wei, Shuyi; Bian, Xiaohui; Christopher, Odong; Xie, Lang (Frontiers in Pharmacology, 2019)
Background: Studies evaluating the prognostic significance of programmed death-ligand 1 (PD-L1) expression in colorectal cancer (CRC) are limited and remain controversial. This meta-analysis was conducted in order to evaluate the clinicopathological and prognostic significance of PD-L1 expression in CRC patients. Methods: A comprehensive search was performed against the Medline/PubMed, Embase, Cochrane Library, Web of Science (WoS) and Scopus databases. Data were extracted with name of the first author, year of publication, country of origin, tumor type, number of cases, staining method, cut-off values, PD-L1 positive expression, clinicopathological parameters, outcome, and quality assessment score, and statistical analysis was conducted using Review Manager Version 5.3 (Revman the Cochrane Collaboration; Oxford, England) and STATA version 14 (Stata Corporation; College Station, TX, USA). Results: Ten studies were included in this meta-analysis, in which the pooled hazard ratio (HR) showed that PD-L1 expression in tumor cells was significantly associated with a poor overall survival (HR=1.50, 95%CI 1.05-2.13, P=0.03). The pooled HR for disease-free survival (DFS) indicated that PD-L1 expression was significantly associated with shorter DFS (HR=2.57, 95%CI 1.40-4.75, P=0.002). The pooled odds ratios (ORs) showed that PD-L1 expression was associated with poor differentiation (OR=3.47, 95%CI 1.37-8.77, P=0.008) and right colon cancer (OR=2.38, 95%CI 1.57-3.60, P<0.0001). However, the expression of PD-L1 was independent of gender, age, tumor size, tumor stage, lymph node metastasis, and tumor-node metastasis stage. Conclusion: This meta-analysis indicated that a high level of PD-L1 expression was a biomarker for poor prognosis in CRC patients. This information may be helpful for clinicians to stratify CRC patients for anti-PD-1/PD-L1 therapy, particularly patients with microsatellite instability high (MSI-H). Well-designed and high-quality studies with uniform evaluation methods were needed to confirm the association of PD-L1 expression in CRC.